The Popular Front in France defending democracy, 1934 - 38 - Jackson, Julian (Cambridge Univ. Pr, 1988)
This is the first full-length study in English of the Popular Front, the left-wing coalition which emerged in France during the 1930s in response to the threat of fascism and which went on to win the elections of 1936, giving France her first socialist premier, Léon Blum. After a brief narrative history of the Popular Front the book is organised thematically around the main historiographical debates to which the Popular Front has given rise. Among the issues considered are the origins of the strikes of 1936, the reasons for the failure of the Popular Front economic policy, the relationship between culture and politics in France in the 1930s and the causes of France's policy of non-intervention in the Spanish Civil War. The book views the Popular Front at three levels - as a mass movement, political coalition and government - and argues that it must not be seen just as a narrowly political phenomenon but as a political, social and cultural explosion which attempted to break down the barriers between all areas of human activity in the highly compartmentalised society of France in the 1930s. Even if the Popular Front ultimately failed in this aim it has acquired legendary status in France, and the epilogue to the book briefly examines the 'myth' of the Popular Front from 1936 to the present day.